Two new species of Picicola Clay & Meinertzhagen, 1938 (Phthiraptera: Philopteridae) from Piciformes (Bucconidae and Galbulidae) in Brazil - Valim, Michel P.; Linardi, Pedro M. (Zootaxa, 2006)
Two new species, Picicola serrafreirei and Picicola galbulica, are described and illustrated from specimens of lice collected from the white-eared puffbird (Nystalus chacuru (Vieillot, 1816)) and the rufous-tailed jacamar (Galbula ruficauda Cuvier, 1816) in Brazil. The morphological relationships of the two new species are discussed. P. serrafreirei is the second species of Picicola recorded from the avian family Bucconidae, while P. galbulica represents the first record from the Galbulidae.